A Human Rights Discourse on Death Penalty for Corruptors during the Outbreaks: Reflection on the Covid 19 Pandemic - Kamalludin, Iqbal; Christia, Adissya Mega; Umar, Achmad Jauhari; Pratami, Bunga Desyana; Widiastuti, Rizqiyani Syifa; Putri, Delasari Krisda (Universitas Negeri Semarang (UNNES), 2023)
The Covid-19 pandemic profoundly impacted Indonesia's stability, yet amidst these challenges, a senior official within the Ministry of Social Affairs engaged in corrupt practices related to social grants, an offense stipulated under Article 2 paragraph (2) of Law No. 20 of 2001, amending Law No. 31 of 1999 on Corruption, which mandates the death penalty. This research examines the tension between imposing the death penalty on corruption offenders during emergencies and the human rights perspective, particularly in Indonesia. Employing a qualitative normative juridical method rooted in criminal law and human rights standards, the study reveals that despite the provision allowing for the death penalty for corruption during Covid-19, Indonesia adopts a moderately particularistic human rights stance that regards human rights as universal principles while addressing national concerns. The study highlights Indonesia's nuanced approach to human rights in the context of criminal justice, particularly concerning the application of the death penalty to corruption offenders during crises. It underscores the country's effort to uphold human rights as universal while recognizing national circumstances. This research contributes to ongoing scholarly debates on the intersection of emergency measures, criminal justice, and human rights, offering insights into how states navigate legal provisions in times of crisis to maintain stability without compromising fundamental rights. The findings provide a critical perspective for policymakers, legal practitioners, and human rights advocates grappling with issues of justice and rights protection amid global emergencies.